Light concentrators for the Sudbury Neutrino Observatory - Doucas, G; Gil, S; Jelley, N; McGarry, L; Moorhead, M; Tanner, N; Waltham, C (1996)
There is an important and growing class of elementary particle detectors which are characterized by a large sensitive volume (thousands of tonnes), very low radioactive backgrounds, and rely on the emission of light for particle detection. Water Cherenkov detectors come into this category; they have a large mass of water as the sensitive medium. Particles are detected when they interact with the water and produce Cherenkov light, so detection efficiency relies on having a huge light sensitive area at the periphery of the detector. The most cost-effective way of achieving this is by placing light concentrators on large photomultiplier tubes (PMTs). This paper describes the work carried out on light concentrators for the PMTs in the Sudbury Neutrino Observatory, a 1000 tonne heavy water Cherenkov detector. We discuss the advantages of using light concentrators, summarize the optical theory of non-imaging light concentration, and describe in detail the development and manufacture of the concentrators themselves.